Dark Sides of Organizational Behavior and Leadership 2019
DOI: 10.5772/intechopen.78790
|View full text |Cite
|
Sign up to set email alerts
|

Dark Side of Leadership in Educational Setting

Abstract: Einstein said that darkness is absence of light. It is assumed that absence of leadership or misappropriation of leadership characteristics and behaviors results in Dark leadership, and it is the system that produces a culture in which dark side of leadership becomes acceptable. In this chapter, I would be exploring the role of middle leadership (school heads, district education officers, and administrative officers) of school education department in Punjab. The chapter is based upon a qualitative study with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 77 publications
(126 reference statements)
1
2
0
Order By: Relevance
“…Therefore, feelings of suppression and oppression are clear from the results of this research, indicated by the negative correlation between teachers' motivation and satisfaction with PAS. Similar oppressed feelings of teachers have been observed in recent research by the author (Arif, 2018;Arif & Iqbal, 2019). The collective results of these studies lead to a single point agenda that policymakers must reflect on the causes of failure in achieving the desired objectives of PAS (improvement in teacher motivation, student achievement); only then the schools' education department of Punjab would be able to realize national goals of quality education.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Therefore, feelings of suppression and oppression are clear from the results of this research, indicated by the negative correlation between teachers' motivation and satisfaction with PAS. Similar oppressed feelings of teachers have been observed in recent research by the author (Arif, 2018;Arif & Iqbal, 2019). The collective results of these studies lead to a single point agenda that policymakers must reflect on the causes of failure in achieving the desired objectives of PAS (improvement in teacher motivation, student achievement); only then the schools' education department of Punjab would be able to realize national goals of quality education.…”
Section: Discussionsupporting
confidence: 85%
“…By analyzing the competence level of teachers, the schools can find discrepancies between the expected and actual performance of teachers that allows them to modify their policies and criteria to reach their goals (Skaalvik & Skaalvik, 2017). The Appraisal system entails the purpose of empowering the school administration to get more control through continuous supervision and evaluation; some would attribute it as 'harassing,' 'bullying,' or even 'policing' the teachers (Arif, 2018;Martin, Fisher-Ari & Kavanagh, 2020).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The list of adverse implications of narcissists in managerial positions can be additionally supplemented with inauspicious outcomes for group performance and decision-making Nevicka, Ten Velden, de Hoogh, & van Vianen [91]; Nigro [92], although in some cases narcissistic admiration may be beneficial to group cohesiveness and social identity Benson, Jeschke, Jordan, Bruner, & Arnocky [93], as well as negative effects on creativity and innovation Henriques, Curado, Jerónimo, & Martins [94], though Strobl [58] report controversial evidence with regards to the latter. In addition, researchers have associated narcissistic leadership with increased risk-taking, selfserving leader behaviours and organisational resource allocation contingent on self-definition as a leader and possessed power Rus [95], establishment of an organisational culture, tolerating narcissistic behaviours Arif [96] and unethical conduct Morais & Randsley de Moura [97], along with a competitive psychological climate Spurk & Hirschi [98], all of these hampering organisational change Neves & Schyns [7]. The ambiguous connotation of the described effects reveals the complex and dynamic nature of the relationship between narcissism and leadership, which may be better understood by consideration of the exact mechanism, underlying the social and psychological interaction between narcissists and their followers in work environments, which can be described with the idealization-devaluation-discard cycle Arabi [45].…”
Section: Annals Of Reviews and Researchmentioning
confidence: 99%